A CASE STUDY OF SRIVALLABHA TEMPLE IN KERALA: THE BRAHMANA TEMPLE DEPENDENTS OF EARLY MEDIEVAL KERALA - K. M., Suresh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study examines the socio-cultural and economic dynamics of the Srivallabha Temple in Kerala during the early medieval period, focusing on the role of Brahmana temple dependents in shaping the region's temple-centric society. The Srivallabha Temple, a prominent Vishnu shrine, served as a nucleus for religious, administrative, and cultural activities, embodying the interconnectedness of spiritual practices and local governance. By analyzing inscriptions, historical records, and temple manuscripts, this research explores the organizational structure of temple administration, highlighting the pivotal role of Brahmana dependents in land management, ritual practices, and the dissemination of Vedic traditions. The study also investigates how the temple acted as a catalyst for economic redistribution, fostering agrarian expansion through land grants and endowments managed by Brahmanical elites. This interaction between the temple and the agrarian economy underscored the integration of religious and material domains in medieval Kerala. Furthermore, the research contextualizes the evolution of temple patronage under royal and local chieftaincies, examining how these dynamics shaped social hierarchies and communal identities. This case study contributes to a deeper understanding of the historical processes that underpinned Kerala's temple-centered society and offers insights into the broader framework of temple economies and Brahmanical authority in South India.